2017
DOI: 10.1186/s13058-017-0816-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating gamma-glutamyl transferase and development of specific breast cancer subtypes: findings from the Apolipoprotein Mortality Risk (AMORIS) cohort

Abstract: BackgroundDifferent etiological pathways may precede development of specific breast cancer subtypes and impact prevention or treatment strategies. We investigated the association between gamma-glutamyl transferase (GGT) and development of specific breast cancer subtypes based on oestrogen receptor (ER), progesterone receptor (PR) and HER2 status.MethodsWe included 231,283 cancer-free women in a Swedish cohort. Associations between GGT and breast cancer subtypes were investigated with nested case–control and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Moreover, evidence summarised in a meta-analysis indicates that increasing levels of GGT and ALT may also be related to incident cancer risk 16. However, the number of included studies for site-specific cancers was limited and only a few further prospective studies on GGT and cancer risks were conducted since then 17–19…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence summarised in a meta-analysis indicates that increasing levels of GGT and ALT may also be related to incident cancer risk 16. However, the number of included studies for site-specific cancers was limited and only a few further prospective studies on GGT and cancer risks were conducted since then 17–19…”
Section: Introductionmentioning
confidence: 99%
“…Aspartate aminotransferase and alkaline phosphatase are both blood biomarkers related to liver function and were not previously associated with non-metastatic breast cancer 59 . In contrast, gamma glutamyltransferase was observed to have positive association with subtypes of breast cancer in the Apolipoprotein Mortality Risk (AMORIS) cohort 60 , and C-reactive protein, a marker of systemic inflammation, was reported to be associated with breast cancer via meta-analysis 61 , 62 . To our knowledge, no previous studies have reported the association of plasma phosphate, sodium in urine or creatinine in urine with breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…GGT is an enzyme located on the cell membrane, primarily involved in glutathione metabolism and amino acid transport ( 24 ). GGT may act as an oxidative stress amplifier, and persistent oxidative stress stimulation can lead to the destabilization of gene stability, disrupting the balance between cell proliferation and apoptosis, thereby affecting tumor formation and progression ( 25 , 26 ). Moreover, the elevation of GGT may indicate increased invasiveness in HCC as it is involved in the survival, proliferation, and migration of tumor cells, thereby promoting tumor spread and growth.…”
Section: Discussionmentioning
confidence: 99%